Cost and affordability of a nutritionally balanced gluten‐free diet: Is following a gluten‐free diet affordable?. Issue 1 (13th March 2015) - Lambert, Kelly; Ficken, Caitlin
Abstract: Aim: To determine the cost and affordability of a gluten‐free healthy food basket for four reference families in Australia. A secondary aim was to determine the price differential between commonly available gluten‐free and gluten‐containing food staples. Methods: Exploratory study using an amalgamation of two commonly used food basket costing methods. Two food basket types were constructed for four common Australian family types. These were designated the Healthy Food Basket and modified (gluten‐free) Healthy Food Basket. Baskets were priced at five locations and costs as a proportion of the Equivalised Household Disposable Income and average weekly earnings for welfare recipients were calculated. The price differential for four common bread and cereal staples were also calculated per 100 g. Results: The gluten‐free healthy food basket was significantly more expensive compared to a gluten‐containing healthy food basket for all family types. The gluten‐free basket was considered unaffordable for three of the four common family types. Gluten‐free staples are significantly more expensive than their gluten‐containing counterparts. Conclusions: Compliance to a gluten‐free diet may be more difficult for some families due to the significant price discrepancy of gluten‐free items. Families on welfare with people who require a gluten‐free diet are particularly vulnerable to food insecurity. Consideration should be given to the creation of a national subsidised medical foods program to enable equitable access to affordable gluten‐free staple foods via prescription.